The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d1cc05964e
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-controlled cobalt-catalyzed remote hydroboration and alkene isomerization of allylic siloxanes

Abstract: The efficient cobalt-catalyzed remote hydroboration and alkene isomerization of allylic siloxanes with pinacolborane were realized by a ligand-controlled strategy. With 1,2-bis(dicyclohexyl-phosphino)ethane as the ligand, the remote hydroboration reactions proceeded well...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Since the first exploration of direct hydroboration of alkenes by Brown in 1956, 6 it has become one of the most powerful tools for forging C–B bonds. 7 Over the past few decades, remarkable efforts have been made in hydroboration reactions that are catalysed by transition metals 8 or visible-light, 9 which are widely used in organic synthesis due to their high catalytic efficiency, high regioselectivity and superior atom economy. Among them, visible-light mediated hydroboration reactions of alkenes with NHC-boranes for preparing α-boryl carbonyl compounds have received increasing attention.…”
mentioning
confidence: 99%
“…Since the first exploration of direct hydroboration of alkenes by Brown in 1956, 6 it has become one of the most powerful tools for forging C–B bonds. 7 Over the past few decades, remarkable efforts have been made in hydroboration reactions that are catalysed by transition metals 8 or visible-light, 9 which are widely used in organic synthesis due to their high catalytic efficiency, high regioselectivity and superior atom economy. Among them, visible-light mediated hydroboration reactions of alkenes with NHC-boranes for preparing α-boryl carbonyl compounds have received increasing attention.…”
mentioning
confidence: 99%
“…The evaluation of ligands showed that the use of bidentate 1,10‐phenanthroline ( L1 ) and 2,2′‐bipyridine ligand ( L2 ) proved inefficient for this transformation (Table 1, entries 2 and 3). Moreover, the ligands L3 and L4 employed in our previous migratory hydroboration [12a,b] gave significantly lower yields with the overwhelming majority of alkyl bromide 1 a recovered (Table 1, entries 4 and 5). It is worth noting that the ligand L5 commonly used in cobalt‐catalyzed migratory hydroboration of alkenes [12b, 13] resulted in poor conversion (Table 1, entry 6).…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the ligands L3 and L4 employed in our previous migratory hydroboration [12a,b] gave significantly lower yields with the overwhelming majority of alkyl bromide 1 a recovered (Table 1, entries 4 and 5). It is worth noting that the ligand L5 commonly used in cobalt‐catalyzed migratory hydroboration of alkenes [12b, 13] resulted in poor conversion (Table 1, entry 6). The survey of solvent effect revealed that the utilization of DMF, DME, and CyH all gave inferior outcomes (Table 1, entries 7–9).…”
Section: Resultsmentioning
confidence: 97%
“…Besides, the evaluation of ligands showed that structurally similar ligand L2 and L3 gave significantly lower regioselectivities (Table 1, entries 4–5), and only a trace amount of the desired product was observed when sterically bulky L4 was used (Table 1, entry 6). Moreover, ligands L5 – L7 previously employed in our migratory hydroborations [11a,b] proved inefficient in this transformation (Table 1, entries 7–9). Notably, modestly excess amount of L1 was indispensable to achieve the satisfactory yield and regioselectivity (Table 1, entry 10).…”
Section: Resultsmentioning
confidence: 99%